MS care: integrating advanced therapies and holistic management - Giovannoni, Gavin; Ford, Helen L.; Schmierer, Klaus; Middleton, Rod; Stennett, Andrea M.; Pomeroy, Ian; Fisniku, Leonora; Scalfari, Antonio; Bannon, Colin; Stross, Ruth; Hughes, Sarah; Williams, Adam; et al. (Frontiers in Neurology, 2024)
Lifestyle and environmental factors are key determinants in disease causality and progression in neurological conditions, including multiple sclerosis (MS). Lack of exercise, poor diet, tobacco smoking, excessive alcohol intake, social determinants of health, concomitant medications, poor sleep and comorbidities can exacerbate MS pathological processes by impacting brain health and depleting neurological reserves, resulting in more rapid disease worsening. In addition to using disease-modifying therapies to alter the disease course, therapeutic strategies in MS should aim to preserve as much neurological reserve as possible by promoting the adoption of a “brain-healthy” and “metabolically-healthy” lifestyle. Here, we recommend self-regulated lifestyle modifications that have the potential to improve brain health, directly impact on disease progression and improve outcomes in people with MS. We emphasise the importance of self-management and adopting a multidisciplinary, collaborative and person-centred approach to care that encompasses the healthcare team, family members and community support groups.